BATAS KEBEBASAN UNJUK RASA DI DKI JAKARTA - Rahmatulloh Rahmatulloh (Jurnal Ilmiah Mimbar Demokrasi, 2017)
This study is paying attention to the limits of free speech in the Province of DKI Jakarta by analyzing the governor’s regulation number 232 of 2015 on control about free speech in public.by the end of 2015. The method used is literature study and documentary analysis. The results of research indicate that governor regulation number 232 year 2015 formally contrary to applicable law, because freedom of speech is the domain of the law as stated in the 1945 Constitution Article 28 J verse 2 and has been regulated in law number 9 of 1998. Other than that governor’s rule contradicts to democratic and good governance principles, because the drafting does not open and involve society, therefore the governor’s rule should not be effective.